Toward Scaled-Up and Sustainable Agriculture Finance and Insurance in Uganda - World Bank (World Bank, Washington, DC, 2019)
In March 2018, Uganda's Ministry of Finance, Planning and Economic Development (MoFPED) formally requested technical assistance from the World Bank Group (WBG) to conduct a technical and diagnostic review of the Uganda Agricultural Insurance Scheme (UAIS) with the objective of providing recommendations to enhance the scalability and sustainability of the scheme going forward. This technical report covers the rapid assessment of agriculture finance and its recommendations, the findings of the situation and gap analysis of the UAIS, and where appropriate, presents the WBG’s recommendations for strengthening the scheme; it also includes a proposal for two additional insurance programs, one for crop and one for livestock, targeted at small-scale farmers. Section one is comprised of four chapters that provide important background information: chapter one provides context for the study; chapter two describes the agricultural sector in Uganda, including the constraints and risk exposure faced by small-scale farmers; chapter three offers an overview of the agriculture finance landscape; and chapter four describes past and present agricultural insurance initiatives, including the UAIS. Section two includes the remaining chapters that present findings and make recommendations for scaling up agriculture insurance in Uganda and making programs sustainable. Specifically, chapter five describes in detail the situation and gap analysis carried out for UAIS insurance products, operating systems and procedures, and underwriting results, and it identifies possible ways to strengthen the scheme for the public-private partnership (PPP) stakeholders to consider. Chapter six presents options for the development of large-scale Area Yield Index Insurance (AYII) to complement the existing UAIS crop insurance products and programs, and it includes fiscal costings for GoU to consider. Chapter seven presents options for the development of large-scale Satellite-Based Pasture Drought Index Insurance (SPDII) for open-grazed livestock in semi-arid regions of Uganda, most notably the Karamoja subregion.